The mechanism of trans-δ-viniferin inhibiting the proliferation of lung cancer cells A549 by targeting the mitochondria - Yin, Ruochun; Zhang, Yiling; Su, Liping; Chen, Dongdong; Lou, Shidi; Luo, Xuecai; Wang, Lin; Tang, Rupei; Zhang, Liang; Tian, Xiaohe (Frontiers in Pharmacology, 2023)
Trans-δ-viniferin (TVN), as a natural extract, is a resveratrol dimer with attractive biological activities particularly its anti-tumor character. Whereas, the mechanism of TVN interfering of cancerous proliferation have not been fully understood. Herein in this work, we have found that TVN could trigger cancerous mitochondrial membrane potential (ΔΨm) reduction with intracellular reactive oxidative species (ROS) level increasing, leading to apoptosis, which made TVN a promising candidate for lung cancer cells A549 treatment. Therefore, this study provided TVN an option to meet the demand for higher antitumor availability with lower biotoxicity and other clinical applications.